The suprachoroidal space: from potential space to a space with potential - Moisseiev E (Dove Medical Press, 2016)
Elad Moisseiev,1–3 Anat Loewenstein,2,3 Glenn Yiu1 1UC Davis Eye Center, University of California Davis, Sacramento, CA, USA; 2Ophthalmology Department, Tel Aviv Medical Center, Tel Aviv, 3Sackler School of Medicine, Tel Aviv University, Tel Aviv, Israel Abstract: Recent advances have made it possible to image the suprachoroidal space, and the understanding of its clinical applications is currently being greatly expanded. This opinion piece covers the advances in imaging techniques that enable the demonstration of the suprachoroidal space, and its implication in various retinal pathologies. It also reviews its potential uses as a route for drug delivery for the treatment of retinal diseases, and its use in innovative surgical techniques. Current research is leading the way for the suprachoroidal space to be an aspect of retinal disease diagnosis, monitoring, medical treatment, and surgical manipulation. Keywords: suprachoroidal space, enhanced depth imaging, drug delivery, potential space